Product Differentiation and Intra-Industry-Trade: Test and Classification Issues on Italian Data - Michele Burattoni; Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1993)
A description of IntraIndustry-Trade is provided for Italy at the finest level of disaggregation of trade flows so far performed in the letterature. Some stylized facts emerge. The most striking is the almost stationary of IIT over the last two decades. The main thrust of the paper is concerned with vertical differentiation as a determinant of trade specialization. We show that IIT can be surely be made to depend on the difference between import and export prices, which is the best rapresentation of vertical differentiation.
Keywords: 330